Editorial - Rezania, Mohammad; Ma, Derek; Sevilla, Ruben (European Journal of Computational Mechanics, 2024)
It is with pleasure to present the UKACM 2023 special issue. The 2023 Annual Conference of the UK Association for Computational Mechanics (UKACM 2023) was hosted by the University of Warwick during 19-21 April 2023 and was attended by researchers from over 30 UK and overseas institutions. With over 70 presentations including keynotes, invited talks and topical sessions as well as Q&As, the conference provided an excellent forum for exchanging ideas on recent advances in different areas related to computational mechanics methods. Following the conference, selected authors were invited to extend their conference papers and submit them for publication in a special issue of the European Journal of Computational Mechanics. The completed special issue includes four papers on different computational mechanics topics. The first paper by Ricketts et al. (2024) investigates the impact of spatially varying boundary conditions due to material heterogeneity in the numerical simulations. It proposes a novel method to apply heterogeneous boundary conditions, especially focusing on moisture transport in unsaturated soils. The method uses Gaussian random fields to model material variability and applies scaled boundary conditions using macro-elements to account for local effects. This approach is validated through simulations, showing that it leads to more natural and realistic system responses compared to traditional methods. The method can be integrated into existing computational codes and is adaptable to various physical systems.